THE INFLUENCE OF JAVANESE ARCHITECTURAL FACADE AND ATMOSPHERE AS A POTENTIAL IN THE CHANGE OF MICE TOURISTS INTO LEISURE TOURISTS - Luh Ayu Perwita Ari Kumara; Ofita Purwani; Agung Kumoro Wahyuwibowo (Universitas Sebelas Maret Surakarta, 2019)
Meetings, Incentives, Conferences and Exhibitions (MICE) is a type of tourism in large groups, planned well in advance, and brought together for a particular purpose. Surakarta as one of MICE destinations in Indonesia has hosted many national and international MICE events. The tourists who do MICE activity in Surakarta are expected to become leisure tourists who will visit Surakarta city anotther time. In order to make MICE tourists become leisure tourists later on, the Convention and Exhibition building which is the place of MICE tourist activity needs to show the elements of Javanese Culture as a means to fulfil their curiosity on the city and to make them want to know more. Showing Javanese Culture can be done not only through the facade of building but also by creating Javanese atmosphere inside the the building. The method is to use questionnare to find out what Javanese objects will be displayed on the facade of building and use Peter Zumthor’s atmosphere design to bring up the cultural atmosphere in the building.